The Independence of the European Central Bank - Ulrike Neyer (Credit and Capital Markets – Kredit und Kapital, 2019)
The ECB is formally independent of instructions from any government. During and after the financial crisis and the acute sovereign debt crisis in the euro area, the ECB has used new instruments and has taken on new tasks and responsibilities. This has led to discussions about the independence of the ECB. Against this background, this paper discusses two questions. First, do the new instruments and tasks imply that the independence of the ECB is under threat? Second, is the use of the instruments and the taking on of the new tasks and responsibilities by an independent institution justified in a democracy or is there a relevant democratic deficit? With respect to these two questions the result of this paper is that especially the Public Sector Purchase Programme (PSPP) and the Single Supervisory Mechanism (SSM) have to be judged critically. – – Die EZB ist formal unabhängig von Weisungen der Regierungen. Während und nach der Finanzkrise und der akuten Staatsschuldenkrise im Euroraum hat die EZB neue Instrumente eingesetzt und neue Aufgaben und Verantwortlichkeiten übernommen, die zu Diskussionen über die Unabhängigkeit der EZB geführt haben. Vor diesem Hintergrund diskutiert diese Arbeit zwei Fragen. Erstens, stellen die neuen Instrumente und Aufgaben der EZB eine Gefahr für ihre Unabhängigkeit dar? Zweitens, ist der Einsatz der neuen Instrumente und die Übernahme der neuen Aufgaben von einer unabhängigen Institution in einer Demokratie zu rechtfertigen, oder besteht ein relevantes Demokratiedefizit? Bezüglich dieser beiden Fragen kommt die Arbeit zu dem Ergebnis, dass insbesondere das Programm zum Ankauf von Anleihen des öffentlichen Sektors (Public Sector Purchase Programme, PSPP) und die von der EZB übernommene Bankenaufsicht (Single Supervisory Mechanism, SSM) kritisch zu beurteilen sind.
Keywords: E42; E52; E58; 330; Central bank independence; Eurosystem; monetary policy; financial crisis; sovereign debt crisis